O Humanismo português e europeu: no 5º centenário do Cicero Lusitanus - Madalena Brito (Outros Títulos, 2020)
The result of a collaboration between the Centre for Classical Studies of the University of Lisbon and the Centre for Classical and Humanistic Studies of the University of Coimbra to celebrate the five hundredth anniversary of the birth of Jerónimo Osório, the book Portuguese and European Humanism. On the 5th centenary of Cicero Lusitanus: Don Jerónimo Osório (1515-1580) brings together the studies of several collaborators from different European universities. In addition to the analysis of the life and work of the Portuguese humanist, namely his literary, historiographic and epistolary production, as well as the treatises on moral and political philosophy and commentaries on biblical texts, this volume also aims to offer an overview of the European Renaissance rooted in the study and reading of classical authors at the time of Jerónimo Osório.